Resistive random access memory structure and preparation method thereof
By introducing a lower interpolation layer and Mn-doped ZnO dielectric layer into the resistive variable memory, the problem of insufficient stability and reliability of the resistive variable memory in the prior art is solved, and a higher resistance-change ratio, maintenance characteristics and magnetism are achieved. Improves the overall performance of the device.
Patent Information
- Application Number
- CN202411424803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
The operating stability and reliability of existing resistive memory are poor, especially due to the weak magnetic properties and poor electrical performance reliability of dilute magnetic semiconductor oxides, which limit their effectiveness in actual storage applications.
By setting a lower interpolation between the semiconductor substrate and the dielectric layer film, using Mn-doped ZnO as the dielectric layer material, a dilute magnetic semiconductor is formed, and a thin film is prepared by pulsed laser deposition method, and oxygen vacancies are introduced to improve resistance performance.
The resistance-change ratio, maintenance characteristics and fatigue characteristics of the resistive-change memory are improved, the magnetic and working stability of the device are improved, the switching voltage distribution is concentrated and significantly reduced, and the resistance-change performance is significantly improved.
Smart Images

Figure CN119486580A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor manufacturing technology, and in particular relates to a resistive random access memory structure and a preparation method thereof. Background Art
[0002] With the advancement of technology, non-volatile memory plays an increasingly important role in people's daily lives. Among the many non-volatile memories, the most noteworthy are the following four new types of non-volatile memories: ferroelectric RAM (FRAM), phase-change RAM (PRAM), magnetoresistive RAM (MRAM) and resistive random access memory (RRAM). RRAM has strong market competitiveness due to its many excellent performances and potential development value. Although it has developed rapidly among new non-volatile memories, it has not yet reached high application requirements in terms of device stability and other aspects. The existing RRAM has a simple structure, similar to the MIM (metal / insulator / metal) three-layer structure of a parallel plate capacitor, that is, a sandwich structure consisting of three parts: a bottom electrode, a resistive layer and a top electrode. Figure 1 The resistive switching layer is generally an insulator or a semiconductor material. The RRAM storage structure is shown in Figure 2 As shown, data storage is achieved by applying a suitable voltage switch to make it in two or more different resistance states (LRS low resistance state, HRS high resistance state). However, what is different from phase change memory is that the resistive material does not undergo a phase transition. In most cases, the local conductive filament formed by the dielectric layer causes the switch HRS to transition to LRS. The breakage of the filament causes the device to transition from LRS to HRS. As a new type of non-volatile memory, RRAM has a simple structure, fast storage speed, high density, long data retention time, and low read and write operation voltage.
[0003] Currently, many literatures report that the magnetism of dilute magnetic semiconductor oxides is weak and the reliability of electrical properties is poor, which limits their practical storage applications as RRAM resistive switching layers. ZnO is a typical direct bandgap wide-bandgap transparent semiconductor oxide, which has great application value and development potential in many fields, especially in optoelectronic applications, such as ultraviolet detectors, transparent conductive films, antistatic films, etc. In recent years, the upsurge in the research of transition metal-doped ZnO dilute magnetic oxides shows that this field is attracting increasing interest, not only because of its promising applications in spin electronics, but also because of its good physical properties.
[0004] Based on the above-mentioned deficiencies of the existing technology, the present technology aims to introduce an oxygen-deficient intercalation layer through the selection of the material system and the optimization of the structural design, adjust the resistive switching properties of the binary metal oxide film by the number and distribution of oxygen vacancies, improve the electrical and magnetic properties of the resistive switching layer of the resistive memory, and thus improve the storage performance of the resistive memory. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a resistive random access memory structure and a preparation method thereof, so as to solve the technical problem that the working stability and reliability of the resistive random access memory are poor.
[0006] One of the above objects of the present invention is achieved by the following technical solution:
[0007] A resistive memory structure, characterized in that: it comprises a semiconductor substrate, on which a lower intercalation layer film, a dielectric layer film and a top electrode are sequentially formed;
[0008] The semiconductor substrate uses a substrate Pt / Ti / SiO2 / Si or FTO as a semiconductor substrate with a bottom electrode;
[0009] The lower intercalation layer thin film material is ZnO, TiO, SiOx or AlOx;
[0010] The dielectric layer film is made of ZnO semiconductor material and is introduced with at least one of the magnetic transition metal elements Mn, Ti, Cr and Ni, with the transition metal doping amount being 1% to 7% at.%;
[0011] The lower intercalation layer and dielectric layer film are prepared on the surface of the semiconductor substrate by a pulse laser deposition method.
[0012] Moreover, the dielectric layer film adopts Mn-doped ZnO to form a dilute magnetic semiconductor.
[0013] The second objective of the present invention is achieved by the following technical solutions:
[0014] A method for preparing a resistive random access memory structure, characterized by comprising the following steps:
[0015] Step 1, preparing a Mn-doped ZnO target by a sol-gel method;
[0016] Step 2, using pulsed laser deposition to successively prepare a lower intercalation layer film and a dielectric layer film on a semiconductor substrate;
[0017] Step 3: On the prepared dielectric layer film, a metal mask plate with circular holes is used to cover the non-prepared area, and a magnetron sputtering coating method is used to prepare a top electrode through the circular holes of the metal mask plate.
[0018] Furthermore, step 1 includes:
[0019] (1) According to the ratio of zinc acetate to manganese acetate, the preparation component is calculated as Zn x Mn y The specific amount of each reagent required for the sample of O, where X+Y=1, Y is 1% to 7% at.%;
[0020] (2) Using ethylene glycol monomethyl ether as a solvent, accurately measuring a certain volume with a measuring cylinder and placing it in a beaker, and accurately weighing the required mass of zinc acetate and manganese acetate crystals with an electronic balance;
[0021] (3) respectively dissolving the crystals weighed in step (2) in a beaker containing ethylene glycol methyl ether, and simultaneously dropping ethanolamine as a stabilizer; then placing the beaker on a magnetic heating stirrer and stirring until the crystals are completely dissolved to obtain a clear solution;
[0022] (4) placing the prepared clarified solution in an electric constant temperature water bath, maintaining the water bath temperature at 90° C. for 48 to 72 hours, until a gel is formed;
[0023] (5) placing the obtained gel in an electric heating blast drying oven, drying at 100° C. for 6 hours, then heating to 220° C. and drying for 24 hours, and finally obtaining a bulky material;
[0024] (6) taking out the bulky material and grinding it thoroughly with an agate mortar, putting the ground powder into a corundum crucible, and placing it in a box-type resistance furnace for calcination; first raising the temperature to 400° C. and holding it for 2 hours to completely decompose and volatilize the organic matter in the powder, and then raising the temperature to 500° C. and holding it for 3 hours; finally, after the sample is naturally cooled to room temperature, taking it out to obtain Mn-doped ZnO powder;
[0025] (7) The obtained powder was thoroughly ground using an agate mortar and then placed in a resistance furnace at 1000°C for 5 hours;
[0026] (8) Grind the sample obtained in step (7) thoroughly until there is no granular feeling when lightly twisted with fingers; then use a powder tablet press to press the ground sample into a disc of set diameter and set thickness under a set pressure; place the pressed disc in a box-type resistance furnace and calcine it at 1000° C. for 12 hours to finally obtain a Mn-doped ZnO target.
[0027] Moreover, in step 1 (8), the set pressing pressure is 10 MP, and the pressed product is a disc having a diameter of about 25 mm and a thickness of about 3 mm.
[0028] Furthermore, step 2 includes:
[0029] (1) Using the semiconductor base as a target substrate, the target substrate is cleaned:
[0030] (2) cleaning the substrate;
[0031] (3) Loading and closing the chamber: first install the deposition target on the target holder, then fix the cleaned substrate on the substrate and place it on the sample holder of the vacuum chamber, and finally close the vacuum chamber;
[0032] (4) Thin film deposition: first use a mechanical pump to draw a low vacuum, and when the vacuum degree reaches below 5Pa, start the molecular pump and continue to draw until the vacuum degree of the vacuum chamber reaches below 5×10-4Pa, turn on the substrate heating power supply, and set the substrate temperature to rise; when the set temperature is reached, check whether to fill the vacuum chamber with working gas according to the preparation conditions, and adjust the pressure of the working gas; set the laser parameters: laser frequency, laser energy and pulse number, etc.; adjust the laser optical path and the distance between the substrate and the target material, and start depositing the thin film; first deposit the lower intercalation layer thin film according to the set parameters; then deposit the dielectric layer thin film according to the set parameters; the target material of the dielectric layer thin film is the target material prepared in step 1;
[0033] (5) Set the annealing temperature and holding time, and anneal the deposited film to improve the crystallinity of the film sample.
[0034] Moreover, the specific cleaning method of step 2 (1) is: firstly polish the substrate with fine sandpaper until there is no black debris on the surface and the entire surface is shiny, and then wipe it three to five times with cotton dipped in acetone, alcohol and deionized water respectively.
[0035] Moreover, the specific cleaning method of step 2 (2) is to clean the substrate with acetone, anhydrous ethanol and deionized water using ultrasonic waves for 10 minutes each.
[0036] Moreover, the specific process of step 3 is: placing a circular hole mask plate with stainless steel material on the prepared film; placing the cleaned and dried mask plate on the film, and covering the area except the holes with the mask plate, and depositing metal onto the film at the opening through a magnetron sputtering system to form a Ti electrode, and sputtering a layer of Ag on the surface of the Ti electrode as a protective layer, and the ZMO-based resistive memory device is completed.
[0037] Moreover, in step 3, the mask thickness is 0.3 mm, the size is about 15 mm×15 mm, the diameter of the circular hole is 0.2 mm, and the center distance of the holes is 0.5 mm.
[0038] Moreover, in step 3, the thickness of the Ti electrode is 100 nm and the diameter is 200 μm; the thickness of the Ag is about 20 to 60 nm.
[0039] The advantages and positive effects of the present invention are:
[0040] The present invention forms a Ti / ZMO-B / Pt device containing a lower intercalation layer by arranging a lower intercalation layer between a semiconductor substrate and a dielectric layer film. For a Ti / ZMO-B / Pt device containing a lower intercalation layer (B represents the lower intercalation layer), the intercalation layer provides a large number of oxygen vacancies, and a small switching voltage is required to control the on and off of the filaments. Under the action of a forward electric field, oxygen vacancies are easily accumulated in the direction of the top electrode to form filaments, and thick filaments are formed along the columnar grain boundaries. Oxygen vacancies are gathered in large quantities with high concentrations, and the number of overlapping polarons with consistent orientation increases, and the device has strong magnetism in LRS. Under a reverse electric field, the filaments are disconnected near the top electrode at the weakest part and transformed to HRS, the oxygen vacancy concentration is reduced, and the bound polaron model (Bound magnetic polarons, BMP) BMP polarons are partially overlapped, and the magnetism is weakened. During LRS, oxygen vacancies are gathered in large quantities, the magnetism of the film is enhanced, and the HRS conductive filaments are only partially broken, and the magnetism of the device HRS is still higher than that of the IS. The switching voltage distribution of the device is concentrated and significantly reduced to about 0.5V; the resistance switching ratio is increased by nearly 78 times; the retention characteristics are increased by about 13 times and the fatigue characteristics are increased by about 18 times; the magnetic properties are increased by about 5 to 8 times, thereby improving the working stability and reliability of the resistive memory. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a simplified diagram of the structure of an existing three-layer resistive random access memory;
[0042] Figure 2 It is a simplified diagram of the existing RRAM storage structure;
[0043] Figure 3 It is a resistance memory structure diagram of the ZMO of the present invention;
[0044] Figure 4 is an IV characteristic curve diagram of the Ti / ZMO / Pt device according to an embodiment of the present invention;
[0045] Figure 5 is the IV characteristic curve of the Ti / ZMO-B1 / Pt device of the embodiment of the present invention;
[0046] Figure 6 is the IV characteristic curve of the Ti / ZMO-B2 / Pt device of the embodiment of the present invention;
[0047] Figure 7 is a Set and Reset voltage distribution diagram of a device according to an embodiment of the present invention;
[0048] Figure 8 is a diagram of device retention characteristics of an embodiment of the present invention;
[0049] Fig. 9 is the fatigue characteristic of the device of the embodiment of the present invention;
[0050] Fig.10 MH curves of IS, HRS and LRS of the device according to the embodiment of the present invention. DETAILED DESCRIPTION
[0051] The structure of the present invention is further described below with reference to the accompanying drawings and by way of examples. It should be noted that the present examples are descriptive rather than restrictive.
[0052] A resistive memory structure, see Figure 3 , including a semiconductor substrate, on which a lower intercalation layer film, a dielectric layer film and a top electrode are sequentially formed;
[0053] The semiconductor substrate uses a substrate Pt / Ti / SiO2 / Si or FTO as a semiconductor substrate with a bottom electrode;
[0054] The lower intercalation layer thin film material can be made of oxide materials such as ZnO, TiO, SiOx, AlOx, etc.
[0055] The dielectric layer film adopts ZnO semiconductor material, introduces at least one of magnetic transition metal elements Mn, Ti, Cr, Ni, and the transition metal doping amount is 1% to 7% at.%; Mn is preferably doped into ZnO to form a dilute magnetic semiconductor, which is used as the dielectric layer (also called resistive layer) material to prepare the conductive film;
[0056] The lower intercalation dielectric layer film is prepared by pulsed laser deposition (PLD) technology, and the Mn-doped ZnO (ZMO) film is used as the resistive switching layer to prepare the corresponding RRAM device.
[0057] The method for preparing a resistive random access memory structure of the present invention comprises the following steps:
[0058] Step 1: Preparation of Mn-doped ZnO target
[0059] The Mn-doped ZnO target was prepared by the sol-gel method, and the steps are as follows:
[0060] (1) Calculate the preparation component to be Zn x Mn y The specific amount of each reagent required for the sample O (calculated according to the ratio of zinc acetate to manganese acetate as x:y (X+Y=1, Y is 1% to 7% at.%, in this embodiment, Y is preferably 4 at.%))
[0061] (2) Using ethylene glycol monomethyl ether as a solvent, accurately measuring a certain volume with a measuring cylinder and placing it in a beaker, and accurately weighing the required mass of zinc acetate and manganese acetate crystals with an electronic balance;
[0062] (3) The crystals weighed in step (2) are dissolved in beakers containing ethylene glycol methyl ether, and ethanolamine (in an amount equal to that of the cation) is added dropwise as a stabilizer; the beaker is then placed on a magnetic heating stirrer and stirred until the crystals are completely dissolved to obtain a clear solution.
[0063] (4) placing the prepared clarified solution in an electric constant temperature water bath, maintaining the water bath temperature at 90° C. for 48 to 72 hours, until a gel is formed;
[0064] (5) placing the obtained gel in an electric heating blast drying oven, drying at 100° C. for 6 hours, then heating to 220° C. and drying for 24 hours, and finally obtaining a bulky material;
[0065] (6) Take out the bulky material and grind it thoroughly with an agate mortar. Put the ground powder into a corundum crucible and place it in a box-type resistance furnace for calcination. First, heat it to 400°C and keep it for 2 hours to completely decompose and volatilize the organic matter in the powder. Then, heat it to 500°C and keep it for 3 hours. Finally, wait for the sample to cool naturally to room temperature and then take it out to obtain Mn-doped ZnO powder.
[0066] (7) The obtained powder was thoroughly ground using an agate mortar and then placed in a resistance furnace at 1000°C for 5 hours;
[0067] (8) The sample obtained in step (7) was fully ground until no particles were felt when lightly twisted with fingers; then, a powder tablet press was used to press the ground sample into a disc with a diameter of about 25 mm and a thickness of about 3 mm under a pressure of 10 MPa; the pressed disc was placed in a box-type resistance furnace and calcined at 1000° C. for 12 hours to finally obtain Mn-doped ZnO (Zn 0.96 Mn 0.04 O) Target (abbreviated as ZMO)
[0068] Step 2, preparing a lower intercalation layer film and a dielectric layer film;
[0069] (1) Cleaning the target substrate (semiconductor base): First, use fine sandpaper to polish the substrate until there is no black debris on the surface and the entire surface is shiny, then wipe it three to five times with cotton dipped in acetone, alcohol and deionized water respectively;
[0070] (2) Cleaning the substrate: Clean the substrate with acetone, anhydrous ethanol and deionized water in sequence using ultrasonic waves for 10 minutes each;
[0071] (3) Loading and closing the chamber: first install the deposition target on the target holder, then fix the cleaned substrate on the substrate and place it on the sample holder of the vacuum chamber, and finally close the vacuum chamber;
[0072] (4) Thin film deposition: First use a mechanical pump to draw a low vacuum. When the vacuum degree reaches below 5Pa, start the molecular pump and continue to pump until the vacuum degree of the vacuum chamber reaches below 5×10-4Pa. Turn on the substrate heating power supply and set the substrate temperature to rise. When the set temperature is reached, check whether to fill the vacuum chamber with working gas according to the preparation conditions and adjust the pressure of the working gas. Set the laser parameters: laser frequency, laser energy, and number of pulses, etc. Adjust the laser optical path and the distance between the substrate and the target material, and start depositing the thin film; first, deposit the ZnO thin film according to the set parameters; then, deposit the Zn according to the set parameters. 0.96 Mn 0.04 O(ZMO) film (parameters see Table 1, Table 2).
[0073] (5) Annealing process: Set the annealing temperature and holding time, and perform annealing treatment on the deposited film to improve the crystallinity of the film sample.
[0074] Table 1 Deposition parameters of ZnO intercalation prepared by PLD
[0075]
[0076] Table 2 Deposition parameters of ZMO thin films prepared by PLD
[0077]
[0078] Step 3: Prepare the top electrode
[0079] Use a metal mask to assist in the preparation of the top electrode: Place a stainless steel circular hole mask on the prepared film. The mask is 0.3mm thick, approximately 15mm×15mm in size, with a circular hole diameter of 0.2mm and a center-to-center spacing of 0.5mm. Place the cleaned and dried mask on the film. All areas except the holes are blocked by the mask. The metal is deposited onto the film at the openings using a magnetron sputtering system to form a Ti electrode with a thickness of approximately 100nm and a diameter of 200μm. A layer of Ag with a thickness of approximately 20 to 60nm is sputtered on the surface of the Ti electrode as a protective layer. At this point, the ZMO-based resistive memory device is complete. Figure 3 .
[0080] Implementation method:
[0081] Pt / Ti / SiO2 / Si <100> The substrate is a thin film substrate, and a device containing a ZnO lower intercalation layer and a Mn-doped ZnO (abbreviated as ZMO) thin film is prepared using PLD technology.
[0082] Three series of devices Ti / ZMO / ZnO / Pt with dielectric layer thickness of about 100nm were prepared. Due to the similar microstructure and other properties of devices with different thicknesses in the same series, three representative devices in the series were prepared, named ZMO, ZMO-B1, ZMO-B2, referred to as the lower intercalation layer (the intercalation layer thickness can be controlled at 3-10nm.), represented by the symbol B. The deposition time for preparing the lower intercalation layer coating can be 10-90s, among which the deposition time of B1 intercalation layer is 33s (intercalation layer thickness is about 5nm), and the deposition time of B2 intercalation layer is 60s (intercalation layer thickness is 7nm).
[0083] The resistive switching characteristics (current-voltage relationship, retention, and fatigue resistance) of Ti / ZMO / Pt and Ti / ZMO / ZnO / Pt devices were tested using semiconductor characteristic measurement equipment.
[0084] The magnetic properties of the samples in three states (IS (Initial State, IS), HRS and LRS) were measured using a comprehensive physical property measurement system (PPMS).
[0085] For Ti / ZMO / Pt and Ti / ZMO-B / Pt devices, the devices exhibit stable bipolar resistive switching behaviors, such as Figure 4 , Figure 5 , Figure 6 The device without ZnO intercalation layer has a large switching voltage and unstable resistance switching performance, a small resistance switching ratio, poor fatigue resistance, and very weak magnetism. The Ti / ZMO-B / Pt device has a significantly larger switching window and a concentrated and significantly reduced switching voltage distribution due to the embedded ZnO lower intercalation layer ( Figure 7 ), the resistance change ratio increased by nearly 78 times, showing excellent retention characteristics ( Figure 8 ) and fatigue properties ( Fig. 9 ).
[0086] Under the action of external electric field, the Ti / ZMO / Pt and Ti / ZMO-B / Pt devices showed the phenomenon of resistance switching cycle accompanied by strong and weak changes in magnetism. The saturation magnetic moment of HRS and LRS was greater than that of IS ( Fig.10 ). However, the magnetic change ratio of the former is smaller, while that of the latter two is larger. For the lower intercalated Ti / ZMO-B / Pt device, the saturation magnetic moment of LRS is increased by about 5 to 8 times compared with that of IS, as shown in Table 3.
[0087] Table 3 Saturation magnetic moments of Ti / ZMO / Pt devices and Ti / ZMO-B / Pt devices
[0088]
[0089] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A resistive random access memory structure, characterized in that: It includes a semiconductor substrate, on which a lower intercalation layer film, a dielectric layer film and a top electrode are sequentially formed; The semiconductor substrate uses a substrate Pt / Ti / SiO2 / Si or FTO as a semiconductor substrate with a bottom electrode; The lower intercalation layer thin film material is ZnO, TiO, SiOx or AlOx; The dielectric layer film is made of ZnO semiconductor material and is introduced with at least one of the magnetic transition metal elements Mn, Ti, Cr and Ni, with the transition metal doping amount being 1% to 7% at.%; The lower intercalation layer and dielectric layer film are prepared on the surface of the semiconductor substrate by a pulse laser deposition method.
2. The resistive random access memory structure according to claim 1, wherein: The dielectric layer film adopts Mn doped ZnO to form a dilute magnetic semiconductor.
3. A method for preparing a resistive random access memory structure according to claim 2, characterized in that: The steps include: Step 1, preparing a Mn-doped ZnO target by a sol-gel method; Step 2, using pulsed laser deposition to successively prepare a lower intercalation layer film and a dielectric layer film on a semiconductor substrate; Step 3: On the prepared dielectric layer film, a metal mask plate with circular holes is used to cover the non-prepared area, and a magnetron sputtering coating method is used to prepare a top electrode through the circular holes of the metal mask plate.
4. The method for preparing a resistive random access memory structure according to claim 3, characterized in that: Step 1 includes: (1) According to the ratio of zinc acetate to manganese acetate, the preparation component is calculated as Zn x Mn y The specific amount of each reagent required for the sample of O, where X+Y=1, Y is 1% to 7% at.%; (2) Using ethylene glycol monomethyl ether as a solvent, accurately measuring a certain volume with a measuring cylinder and placing it in a beaker, and accurately weighing the required mass of zinc acetate and manganese acetate crystals with an electronic balance; (3) respectively dissolving the crystals weighed in step (2) in a beaker containing ethylene glycol methyl ether, and simultaneously dropping ethanolamine as a stabilizer; then placing the beaker on a magnetic heating stirrer and stirring until the crystals are completely dissolved to obtain a clear solution; (4) placing the prepared clarified solution in an electric constant temperature water bath, maintaining the water bath temperature at 90° C. for 48 to 72 hours, until a gel is formed; (5) placing the obtained gel in an electric heating blast drying oven, drying at 100° C. for 6 hours, then heating to 220° C. and drying for 24 hours, and finally obtaining a bulky material; (6) taking out the bulky material and grinding it thoroughly with an agate mortar, putting the ground powder into a corundum crucible, and placing it in a box-type resistance furnace for calcination; first raising the temperature to 400° C. and holding it for 2 hours to completely decompose and volatilize the organic matter in the powder, and then raising the temperature to 500° C. and holding it for 3 hours; finally, after the sample is naturally cooled to room temperature, taking it out to obtain Mn-doped ZnO powder; (7) The obtained powder was thoroughly ground using an agate mortar and then placed in a resistance furnace at 1000°C for 5 hours; (8) Grind the sample obtained in step (7) thoroughly until there is no granular feeling when lightly twisted with fingers; then use a powder tablet press to press the ground sample into a disc of set diameter and set thickness under a set pressure; place the pressed disc in a box-type resistance furnace and calcine it at 1000° C. for 12 hours to finally obtain a Mn-doped ZnO target.
5. The method for preparing a resistive random access memory structure according to claim 4, characterized in that: In step 1 (8), the set pressing pressure is 10 MP, and the pressed product is formed into a disc having a diameter of about 25 mm and a thickness of about 3 mm.
6. The method for preparing a resistive random access memory structure according to claim 3, characterized in that: Step 2 includes: (1) Using the semiconductor base as a target substrate, the target substrate is cleaned: (2) cleaning the substrate; (3) Sample loading and chamber closing: first install the deposition target on the target holder, then fix the cleaned substrate on the substrate and place it on the sample holder of the vacuum chamber, and finally close the vacuum chamber; (4) Thin film deposition: first use a mechanical pump to draw a low vacuum, and when the vacuum degree reaches below 5Pa, start the molecular pump and continue to draw until the vacuum degree of the vacuum chamber reaches below 5×10-4Pa, turn on the substrate heating power supply, and set the substrate temperature to rise; when the set temperature is reached, check whether to fill the vacuum chamber with working gas according to the preparation conditions, and adjust the pressure of the working gas; set the laser parameters: laser frequency, laser energy and pulse number, etc.; adjust the laser optical path and the distance between the substrate and the target material, and start depositing the thin film; first deposit the lower intercalation layer thin film according to the set parameters; then deposit the dielectric layer thin film according to the set parameters, wherein the target material of the dielectric layer thin film is the target material prepared in step 1; (5) Set the annealing temperature and holding time, and anneal the deposited film to improve the crystallinity of the film sample.
7. The method for preparing a resistive random access memory structure according to claim 6, wherein: The specific cleaning method of step 2 (1) is: first, polish the substrate with fine sandpaper until there is no black debris on the surface and the entire surface is shiny, and then wipe it three to five times with cotton dipped in acetone, alcohol and deionized water respectively.
8. The method for preparing a resistive random access memory structure according to claim 6, characterized in that: The specific cleaning method of step 2 (2) is to clean the substrate with acetone, anhydrous ethanol and deionized water in turn using ultrasonic waves for 10 minutes each.
9. The method for preparing a resistive random access memory structure according to claim 3, characterized in that: The specific process of step 3 is as follows: a circular hole mask made of stainless steel is placed on the prepared film; the cleaned and dried mask is placed on the film, and the area except the holes is covered by the mask. The metal is deposited onto the film at the opening through a magnetron sputtering system to form a Ti electrode. A layer of Ag is sputtered on the surface of the Ti electrode as a protective layer, and the ZMO-based resistive memory device is completed.
10. The method for preparing a resistive random access memory structure according to claim 9, characterized in that: In step 3, the mask thickness is 0.3 mm, the size is about 15 mm×15 mm, the diameter of the circular hole is 0.2 mm, and the center spacing of the holes is 0.5 mm; the thickness of the Ti electrode is 100 nm, the diameter is 200 μm; the thickness of Ag is about 20 to 60 nm.
Citation Information
Cited By
Controllable crystal orientation SnS2 resistive random access memory and preparation method thereof
CN121985735A